Transcriptomic analysis of adaptive mechanisms in response to inland saline-alkaline water in the mud crab, Scylla paramamosain - Liang, Guoling; Qin, Kangxiang; Chen, Yuhao; Niu, Mingming; Wang, Huan; Wang, Chunlin; Mu, Changkao; Chen, Lizhi; Wang, Fangfang; Su, Qiong; Zhu, Ritong (Frontiers in Marine Science, 2022)
Scylla paramamosain is an important marine aquaculture crustacean on the southeastern coast of China. Given the difficulties of overcrowded coastal aquaculture space and insufficient production, inland saline-alkaline water culture has the potential to alleviate this bottleneck. This study separated 600 crabs into four groups: normal salinity (12-18 ppt, NS), coastal low salinity (3-5 ppt, CS), inland low salinity saline-alkaline (1.5 ppt, IS), and acute low salinity (23 ppt down to 3 ppt, AS), followed by a transcriptomic analysis of the gills. CS-vs-NS, IS-vs-NS, and AS-vs-NS obtained 1154, 1012, and 707 DEGs, respectively. GO analysis showed that the DEGs of the three comparison groups were mainly involved in cellular process, metabolic process, biological regulation, organelle, membrane, extracellular region, binding, and catalytic activity. The findings demonstrate that a significant number of genes are engaged in controlling metabolic processes in the osmoregulation process, and that cell membrane catalysis and different enzymes play a vital part in the environmental adaption process. KEGG enrichment analysis revealed that IS possesses a considerable number of signaling pathways that play important roles in osmoregulation when compared to NS. The cAMP signaling pathway increased the expression of CaM and Na+/K+-ATPase. These findings show that cations like Ca2+, Na+, and K+ are critical for S. paramamosain to adapt to inland low salinity saline-alkaline water, and that the cAMP signaling pathway regulates their levels. This research provides a theoretical foundation for improving the saline-alkaline aquaculture technology of S. paramamosain.